Optimalisasi Tugas Dan Fungsi Bhabinkamtibmas Dalam Menyelesaikan Perkara Ringan Melalui Metode Problem Solving - Ardianingrum, Ajeng Ayu (Indonesian Journal of Police Studies, 2017)
In the last 3 months, minor cases that occurred in the District of Sukamakmur have increased but not significant. In this case Bhabinkamtibmas has a role in resolving these light cases through the Problem Solving method. But in its implementation Bhabinkamtibmas in resolving minor cases through the Problem Solving method is not yet optimal. This study aims to describe the implementation, the factors that influence it, and the expected efforts in optimizing Bhabinkamtibmas in resolving light cases through the Problem Solving method. The research location was in the Sukamakmur Police Station, Bogor District Police with the focus of the Bhabinkamtibmas Problem Solving method in resolving light cases. This study uses qualitative methods with descriptive techniques. Using data triangulation (Moleong; 2006: 330) 4 (four) kinds of techniques, namely sources, theories and techniques as well as primary, secondary and tertiary data sources. Data validity is data reduction, data display, conclusion drawing and verification. This research uses legal structure theory, achievement motivation theory, and the role theory and the concept of Bhabinkamtibmas, the concept of Problem Solving, and the concept of light cases. The implementation of the functions and duties of Bhabinkamtibmas in resolving minor cases through the less optimal Problem Solving Method was analyzed from the concept of Bhabinkamtibmas through perap No. 3 of 2015 concerning Community Policing. In the implementation of light case resolution through the Problem Solving Method, there are internal factors that influence are people, budget, infrastructure and methods, and external factors that influence are public awareness and factors of other functions as well as efforts made in the form of efforts to guide pathways and relationship efforts and work procedures. In the implementation of light case resolution through the Problem Solving Method, the expected effort is the role of Bhabinkamtobmas through achievement motivation theory and the role of FKPM and the disputing community. The conclusion is the implementation of Bhabinkamtibmas in settling minor cases through the less optimal Problem Solving Method due to the double occupation of tasks, as well as inadequate Bhabinkamtibmas personnel and the review of tasks that are not in accordance with Perkap No. 3 of 2015 concerning Community Policing. The inhibiting factors of Bhabinkamtibmas in resolving minor cases through the Problem Solving Method are the organizational structure, HR, Sarpras and dukops of Sukamakmur Sector Police which have not been fulfilled. And the expected role in optimizing the implementation of light case resolution through the Problem Solving Method from each party. Keywords: Optimization, Bhabinkamtibmas.